Production performance and estimation of genetic parameters of production traits in Sahiwal cattle at an organized herd - Ratwan, Poonam (Indian Journal of Dairy Science, 2018)
The information on the first lactation milk production traits of Sahiwal cattle maintained at an organized herd of ICAR-National Dairy Research Institute, Karnal, India over a period of 29 years (1988-2016) were utilized in the present study. The effect of various genetic and non-genetic factors on first lactation milk production traits and their genetic control was assessed by using mixed model least-squares analysis. The overall least-squares means for first lactation milk production traits viz., 305 days or less milk yield (305DMY), total milk yield (TMY), lactation length (LL), wet average (WA), peak yield (PY), days to attain peak yield (DPY) and dry period (DP) were 1900.42 ± 93.39 kg, 2158.86 ± 115.37 kg, 318.76 ± 12.05 days, 6.73 ± 0.24 kg/day, 10.60 ± 0.31 kg, 54.01 ± 2.34 days and 121.50 ± 10.40 days, respectively in Sahiwal cattle. Analysis of variance showed that the differences were statistically significant (P